Pengalaman Tenaga Kesehatan dalam Memberikan ASI Eksklusif pada Masa Pandemi Covid-19 - Tetik Nurhayati; Novi Enis Rosuliana; Kusmiyati Kusmiyati (Jurnal Penelitian Kesehatan SUARA FORIKES, 2024)
The impact of the Covid-19 pandemic affects all groups, including mothers who work in hospitals who are breastfeeding. Nursing mothers who work in hospitals can still provide exclusive breast milk to their babies, even during the Covid-19 pandemic. The aim of this research was to determine the experience of working mothers in providing exclusive breastfeeding during the Covid-19 pandemic. This type of research was a phenomenological study, which involves 6 participants, namely breastfeeding mothers who work and had babies under three years of age and work in the treatment room at Dr. Hospital. Soekardjo, Tasikmalaya. The collected data was analyzed thematically. The results of this research obtained 6 categories or themes regarding the experiences of working mothers in providing exclusive breastfeeding, namely the mother's knowledge about exclusive breastfeeding and expressed breast milk, the mother's motivation in providing exclusive breastfeeding during the Covid-19 pandemic, the efforts made by the mother in providing exclusive breastfeeding, family support. and workplace support in providing exclusive breastfeeding. It was concluded that an overview had been obtained for health workers to be able to increase self-confidence in providing exclusive breastfeeding for working mothers.Keywords: exclusive breastfeeding; Covid-19; experience; working mother ABSTRAK Dampak dari pandemi Covid-19 mengenai semua golongan, tidak terkecuali ibu yang bekerja di rumah sakit yang saatnya memberikan ASI. Ibu menyusui yang bekerja di rumah sakit tetap dapat memberikan ASI eksklusif pada bayinya, sekalipun dalam masa pandemi Covid-19. Tujuan penelitian ini adalah untuk mengetahui pengalaman  ibu bekerja dalam memberikan ASI eksklusif pada masa pandemi Covid-19. Jenis penelitian ini adalah studi fenomenologi, yang melibatkan 6 partisipan yakni ibu  menyusi yang bekerja dan memiliki bayi dengan usia  di bawah tiga tahun dan bekerja di ruang perawatan di Rumah Sakit Dr. Soekardjo, Tasikmalaya. Data yang terkumpul dianalisis secara tematik. Hasil penelitian ini mendapatkan 6 kategori atau tema tentang pengalaman  ibu bekerja dalam memberikan ASI eksklusif yaitu pengetahuan ibu tentang ASI eksklusif dan ASI perah,  motivasi ibu dalam pemberian ASI eksklusif pada masa pandemi Covid-19, upaya yang dilakukan ibu dalam memberikan ASI eksklusif, dukungan keluarga dan dukungan tempat kerja dalam memberikan ASI eksklusif.  Disimpulkan bahwa telah didapatkan gambaran bagi tenaga kesehatan untuk dapat meningkatkan keyakinan diri dalam pemberian ASI eksklusif bagi ibu bekerja.Kata kunci: ASI eksklusif; Covid-19; pengalaman; ibu bekerja